PEMILIHAN ALTERNATIF PERBAIKAN PERKERASAN JALAN PADA PERSIMPANGAN JALAN DENGAN MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS (STUDI KASUS: SIMPANG EMPAT BUNTU KABUPATEN BANYUMAS) - Agung Susanto; Pratikso Pratikso; Henny Pratiwi Adi (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2023)
The economic growth in Banyumas Regency, Central Java, and its surroundings, followed by the increasing number of vehicles crossing the area. Among the national roads in Banyumas, the Buntu intersection area is one that requires attention. Data collection was conducted by interviewing and filling out questionnaires directly from respondents. In considering the priority of road repairs, there are 11 criteria used in this study. The alternatives that can be done are asphalt pavement, concrete pavement, and concrete - asphalt pavement. The method used in this study uses the Analytical Hierarchy Process (AHP) method with the help of Expert Choice 11 software. Results of field survey indicated the types of road damage that occurred at the intersection of four dead ends in Banyumas Regency, the Sampang-Buntu section were ruts, potholes, wear (polished aggregate) while for the Buntu section-South Kedu the types of damage include alligator cracking, ruts, potholes, stripping. Concrete pavement repair is the main choice because the Buntu intersection is a national road whose daily traffic is traversed by heavy vehicles with the heaviest axle loads above 10 tons, such as buses or large trucks so that respondents want road pavement repairs at crossroads to prioritize traffic average daily.